Strong, superelastic and multifunctional SiC@ pyrolytic carbon nanofibers aerogels. (15th June 2022) - Lu, De; Niu, Min; Zhuang, Lei; Su, Lei; Guo, Pengfei; Gao, Hongfei; Xu, Liang; Cai, Zhixin; Li, Mingzhu; Peng, Kang; Wang, Hongjie
Abstract: Aerogels with reversible compressibility and adjustable electronic property are critical in the fields of pressure sensing and organic absorbing. However, the practical applications are usually limited by the narrow detective pressure range and poor durability. Here, we report facile synthesis of SiC@ pyrolytic carbon (PyC) nanofibers aerogels (SiC@ PyC NFAs) that are simultaneously superelastic and mechanically strong. The sample with ultralow density of 40 mg cm −3 can recover completely from 90% strain and exhibits high compressive stress up to 2 MPa. This is mainly owning to good connections among the SiC nanofibers by rich PyC nodes in the network. Viscoelasticity of the SiC@ PyC NFAs is immune to frequency (1–100 Hz) and temperature (−120 to 300 °C). In addition, the SiC@ PyC NFAs exhibit stable and sensitive resistance response, as well as the capacity to rapidly absorb various organic solvents. These attractive features render the SiC@ PyC NFAs promising candidates for applications as damping or pressure sensors in harsh environments. Graphical abstract: Owning to the formation of abundant PyC nodes inside the fibrous network and the local ordered graphene‒like fragments of PyC, the SiC@ PyC NFAs exhibit superelasticity of completely recovery from 90% strain and high compressive stress up to 2 MPa at ultralow density (40 mg cm −3 ), as well as excellent fatigue resistance. Image 1